PENGARUH HUBUNGAN SOSIAL DI LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR GEOGRAFI PADA SISWA KELAS XI IPS DI SMAN 1 AMPEK ANGKEK KABUPATEN AGAM - Putri, Indah Karina; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
This study aims to analyze (1) the effect of social relations between students and students in the school environment on geography learning outcomes (2) the effect of social relations between students and teachers in the school environment on geography learning outcomes (3) the influence of social relations between students and students and students and teachers in the school environment with the results of studying geography in class XI IPS students at SMA N 1 Ampek Angkek, Agam Regency. The method used in this research is a quantitative method with a correlational type of research. The population of this study were all students of class XI Social Sciences at SMAN 1 Ampek Angkek, Agam Regency. The sample was drawn using a random sampling technique with a total sample of 64 students. The data collection method was obtained from data collected from questionnaires and documentation. The data analysis technique is in the form of multiple correlation analysis techniques. The results showed that (1) the social relationship between students and students towards geography learning outcomes at school had a positive relationship which was included in the very weak category with a correlation result of 0.044369469 (2) social relations between students and teachers at school in geography subjects there is a positive relationship which is included in the very weak category with a correlation result of 0.022289085 (3) Social relations of students towards geography learning outcomes at SMAN 1 Ampek Angkek, Agam Regency, there is a positive relationship which is included in the very weak category with a correlation result of 0.02978263. From the results of the study it can be concluded that the social relations that occur in the school environment are not the main factor influencing student learning outcomes.